2017
DOI: 10.1097/pas.0000000000000772
|View full text |Cite
|
Sign up to set email alerts
|

DUX4 Immunohistochemistry Is a Highly Sensitive and Specific Marker for CIC-DUX4 Fusion-positive Round Cell Tumor

Abstract: The histologic differential diagnosis of pediatric and adult round cell tumors is vast and includes the recently recognized entity CIC-DUX4 fusion-positive round cell tumor. The diagnosis of CIC-DUX4 tumor can be suggested by light microscopic and immunohistochemical features, but currently, definitive diagnosis requires ancillary genetic testing such as conventional karyotyping, fluorescence in situ hybridization, or molecular methods. We sought to determine whether DUX4 expression would serve as a fusion-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 19 publications
1
39
1
Order By: Relevance
“…Ewing sarcoma, alveolar rhabdomyosarcoma, synovial sarcoma, desmoplastic small round cell tumor) did not. 27 DUX4 gene is located within the D4Z4 macrosatellite repeat region (11–100 copies of the repeat units) of the chromosomes 4 and 10 subtelomeric regions. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Ewing sarcoma, alveolar rhabdomyosarcoma, synovial sarcoma, desmoplastic small round cell tumor) did not. 27 DUX4 gene is located within the D4Z4 macrosatellite repeat region (11–100 copies of the repeat units) of the chromosomes 4 and 10 subtelomeric regions. 28 …”
Section: Discussionmentioning
confidence: 99%
“…CIC alterations have also been reported in “Ewing‐like tumors,” with the most common fusion partner being DUX4 . These tumors are characterized by a predominately small round blue cell morphology, often with focal cell spindling, nuclear atypia, and stromal changes …”
Section: Novel and Rare Fusion Events In Pediatric Gliomasmentioning
confidence: 99%
“…Morphologically, CIC‐DUX4 sarcoma shows more varied cytomorphology, often with areas of epithelioid or spindled cells. A monoclonal antibody directed against a conserved region present in both DUX4 homologs (encoded on either 4q35 or 10q26) has recently been investigated in a small series . The authors demonstrated diffuse nuclear staining in all cases, whereas all other round cell tumors were negative.…”
Section: Gene Fusionsmentioning
confidence: 99%